Hidroxiapatitas de ferro e cobre: Aplicações na Redução Catalítica de Óxido de Nitrogênio e na adsorção de moléculas aromáticas heterocíclicas - Magalhães, Mayara de Sousa Oliveira (2020)
Hydroxyapatite (Hap) has been widely used as an alternative in applications such as bioceramics, catalysts and adsorbents for soil and water decontamination due to its interaction with cations and anions in the process of adsorption/ion exchange. In addition, due to its excellent stability hydroxyapatite readily accepts ionic replacements in its structure. This work aims to prepare, characterize and evaluate copper and iron-doped hydroxyapatites in studies for selective catalytic reduction of NO using NH3 as a reducing agent, in addition to studying the adsorption of thiophene, pyrrole and furan in a liquid medium. The hydroxyapatites, both pure and doped with copper and iron, were obtained by the precipitation method. The characterization was performed by the techniques of FAAS, MEV, FTIR, DRX, Mössbauer, solid UV/VIS, BET, TG, and acidity by adsorption of pyridine. The catalytic conversion efficiency of NO was determined in a laboratory catalytic unit from a simulated diesel vehicle exhaustion containing 1000 ppm NO, 1000 ppm NH3 and 2.5% O2 (vol.) He balanced. The stability of the catalysts was evaluated in the presence of SO2 (50 ppm) and/or H2O (10 vol%). In the adsorption studies, equilibrium and adsorption kinetics tests were performed. The equilibrium data received mathematical treatment according to the isotherms of Langmuir, Freundlich and Sips. The kinetic results were modeled according to Weber and Moris and pseudo 1st and 2nd order diffusion equations. After impregnations results showed contents of 1.5 to 6.5% of metal (Cu or Fe), and this incorporation barely affected the materials structure. NH3-SCR studies showed that the metal-free hydroxyapatite matrix had no catalytic activity, whereas materials doped with the highest Ca/Metal (9) molar ratios reached about 90% conversion at 400 oC. The material containing copper was the most promising one in the catalytic process and stable in the presence of SO2 and H2O. In the adsorption equilibrium, the Sips model was the one that best estimated the adsorption capacities for the evaluated materials. In the adsorption kinetics tests, the pseudo first order model was the one that best described the experimental results. The Monte Carlo simulation showed that, in the single component systems, electrostatic repulsion disfavored the efficiency of adsorption of the heterocylic aromatic molecules studied, whereas in the ternary system the phenomenon of mass transport of molecules of furan, pyrrole and thiophene in the solvent must be taken into consideration. In both processes the order of catalytic and adsorptive activity was of the type: HapCu ≈ HapFe> Hap.